PRESENTATION FORM OF JIDUR TRADITIONAL ART IN ULAK DABUK VILLAGE, EMPAT LAWANG REGENCY - Bella Sapira Bella Sapira (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to describe the presentation form of Jidur traditional art in Ulak Dabuk Village, Empat Lawang Regency. The research employed a descriptive qualitative method using observation, interviews, and documentation techniques to collect the data. The informants in this study consisted of the leader of the Jidur art group, musicians, dancers, and community members who were directly involved in the performance activities. The results of the study showed that Jidur art is a traditional ensemble performance that combines musical instruments, vocal pantun performances, and dance movements into a unified presentation. The musical instruments used in the performance include jidur, ketipung, and gong, which create repetitive and dynamic rhythmic patterns. The structure of the performance consists of three stages, namely the opening section, the core section, and the closing section. In the main section, pantun lyrics are delivered spontaneously according to the performance situation using both the Empat Lawang local language and Indonesian. In addition, the interaction between performers and audiences creates a lively and communicative atmosphere during the performance. Jidur art continues to be preserved and performed in traditional ceremonies, cultural festivals, and government events as part of regional cultural preservation and the maintenance of local identity.